2018
DOI: 10.1186/s13014-018-1038-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival of rats bearing advanced intracerebral F 98 tumors after glutathione depletion and microbeam radiation therapy: conclusions from a pilot project

Abstract: BackgroundResistance to radiotherapy is frequently encountered in patients with glioblastoma multiforme. It is caused at least partially by the high glutathione content in the tumour tissue. Therefore, the administration of the glutathione synthesis inhibitor Buthionine-SR-Sulfoximine (BSO) should increase survival time.MethodsBSO was tested in combination with an experimental synchrotron-based treatment, microbeam radiation therapy (MRT), characterized by spatially and periodically alternating microscopic dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…To conduct the in vivo experiments with respect to orthotopic glioma progression and onset of tumor-related seizures, a robust animal model was needed. F98 glioma in Fischer rats is a wellestablished glioma model (Belloli et al, 2013;Schültke et al, 2018;Wang et al, 2018), but to the best of our knowledge, no data about its tumor-associated epileptiform phenotype have been published so far (Kirschstein and Köhling, 2016). The results of our studies suggest that F98 glioma led to interictal epileptiform events (e.g., spikes and spike-waves), indicating a high susceptibility to develop seizures, which was also demonstrated by video-EEG analysis.…”
Section: Discussionsupporting
confidence: 66%
“…To conduct the in vivo experiments with respect to orthotopic glioma progression and onset of tumor-related seizures, a robust animal model was needed. F98 glioma in Fischer rats is a wellestablished glioma model (Belloli et al, 2013;Schültke et al, 2018;Wang et al, 2018), but to the best of our knowledge, no data about its tumor-associated epileptiform phenotype have been published so far (Kirschstein and Köhling, 2016). The results of our studies suggest that F98 glioma led to interictal epileptiform events (e.g., spikes and spike-waves), indicating a high susceptibility to develop seizures, which was also demonstrated by video-EEG analysis.…”
Section: Discussionsupporting
confidence: 66%
“…F98 glioma cells and C6 cells, implanted respectively in Wistar and Fisher rats, were used to demonstrate that two orthogonal, cross-planar MRT arrays (24.75 µm; 211 ctc; 350 Gy peak-dose) significantly increased survival as compared to untreated controls [40]. This effect was amplified when MRT was preceded by the administration of the glutathione synthesis inhibitor buthionine-SR-sulfoximine [41]. When two orthogonal MRTs (50 µm; 200 ctc; 241 Gy peak-dose and 10.5 Gy valley-dose) were compared to two orthogonal BB fields (10.5 Gy), MRT was more effective than BB in slowing F98 glioma growth and increasing tumour vessel permeability [42].…”
Section: Gliomamentioning
confidence: 99%
“…Given that PVDRs are likely to be lower for human treatments [91], a strategy which relies on relatively low peak-dose (100-250 Gy) by leveraging the immunomodulatory [29,53] or angio-disruptive effects of MRT [42,70] could strike an optimal balance between toxicity and tumour control. Previous studies have shown MRT to be effective for treating rat models of glioma when combined with chemotherapeutic agents [36,37,41] or immunotherapy [39]. Future studies should investigate the optimal dose, sequencing and timing of MRT in relation to chemotherapy and immunotherapy and whether there is a role for temporally fractionating the delivery of MRT.…”
Section: Identifying Optimal Targets and Strategies For Mrtmentioning
confidence: 99%
“…A more accurate delineation of the BTV might be possible by using a small animal PET scanner with better spatial resolution. Secondly, taking into account the humane endpoints, several animals had to be euthanized early due to clinical deterioration as result of large tumors as previously described by Schültke et al [44]. This issue will influence the average values significantly.…”
Section: Discussionmentioning
confidence: 99%